2019
DOI: 10.1515/bjes-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do Transition Countries Converge towards the European Union?

Abstract: The aim of this paper is to analyze if the Western Balkan and Eastern Partnership countries converge towards the twenty-eight members of the European Union. The relationships between the selected macroeconomic variables and per capita GDP growth rate are econometrically tested to support this research. The analyzed period is 2004–2017, with two sub-periods: 2004–2008 and 2009–2013. The subdivision is made to test whether the recent financial crisis affected the absolute and conditional convergence process in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This research has shown that the inflation rate can have both positive and negative effects on per capita GDP growth. Theoretically, it should have a negative effect, as confirmed by Yin et al (2003), Vojinović et al (2009), Stoica et al (2019), and Siljak and Nagy (2019), but low, stable inflation is always desirable. Its positive effects on growth are found by Hasanov (2010) and Kryeziu and Durguti (2019).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This research has shown that the inflation rate can have both positive and negative effects on per capita GDP growth. Theoretically, it should have a negative effect, as confirmed by Yin et al (2003), Vojinović et al (2009), Stoica et al (2019), and Siljak and Nagy (2019), but low, stable inflation is always desirable. Its positive effects on growth are found by Hasanov (2010) and Kryeziu and Durguti (2019).…”
Section: Resultsmentioning
confidence: 89%
“…The research hypotheses, which are based on earlier own research (Siljak, 2018;Siljak and Nagy, 2019) and the following literature review, are tested in the paper: H1: Monetary union membership has had a positive impact on the convergence process in the EU; H2: The absolute convergence process of the Eurozone new Member States towards the core countries (EU-14+1) is faster, compared to the non-Eurozone Member States; H3: The absolute and conditional convergence rates are the lowest during the crisis period for both groups of countries.…”
Section: Introductionmentioning
confidence: 99%
“…We can also observe that the impact of the crisis on the Western Balkan countries follows the general European (and global) trends, but with a certain time lag of a year behind the development of the crisis in the EU and the subsequent stabilization and recovery there. It can be stated that the Western Balkan countries' business cycles are in line with the European Union's business cycle; the 2008-2009 crisis affected negatively GDP growth and convergence [Siljak -Nagy, 2019]. After the crisis, we can observe lower economic growth than before and a more permanent decline in the case of Serbia, which recovered later from the crisis.…”
Section: Economic Convergence Development and Potentialmentioning
confidence: 78%